Book review: Trenin, D. (2021). New Balance of Power: Russia in Search of Foreign Policy Equilibrium. Moscow: Alpina Publisher, 471 p. (In Russian) - Maksim A. Nikulin (Vestnik RUDN. International Relations, 2021)
-